2020
DOI: 10.1101/2020.08.20.258632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for CDK7 activation by MAT1 and Cyclin H

Abstract: CDK7, Cyclin H, and MAT1 form the heterotrimeric CDK activating kinase (CAK) complex. CAK is a vital factor for the two essential processes of transcription and cell cycle control. When associated with the general transcription factor II H (TFIIH) it activates RNA polymerase II by hyperphosphorylation of its C-terminal domain (CTD). In the absence of TFIIH it phosphorylates the T-loop of CDKs that control cell cycle progression. CAK holds a special position among the CDK branch due to this dual activity and t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Phosphorylation of the activation loop of CDK1 occurs in trans by a trueC¯DKtruea¯ctivating0.5emtruek¯inase (CAK). In metazoans, CDK1 is activated by the CDK7:Cyclin‐H kinase, 11,12 which is also implicated, as a module of TFIIH, in the phosphorylation of the C‐terminal domain of RNA polymerase II, as recently depicted 13–16 . Whereas metazoan CAK consists of a CDK7:Cyclin‐H complex, activation of the budding yeast CDK1 (Cdc28) is mediated by the distantly related and monomeric CAK1 (hereafter scCAK1) 17–19 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Phosphorylation of the activation loop of CDK1 occurs in trans by a trueC¯DKtruea¯ctivating0.5emtruek¯inase (CAK). In metazoans, CDK1 is activated by the CDK7:Cyclin‐H kinase, 11,12 which is also implicated, as a module of TFIIH, in the phosphorylation of the C‐terminal domain of RNA polymerase II, as recently depicted 13–16 . Whereas metazoan CAK consists of a CDK7:Cyclin‐H complex, activation of the budding yeast CDK1 (Cdc28) is mediated by the distantly related and monomeric CAK1 (hereafter scCAK1) 17–19 …”
Section: Introductionmentioning
confidence: 98%
“…In metazoans, CDK1 is activated by the CDK7:Cyclin-H kinase, 11,12 which is also implicated, as a module of TFIIH, in the phosphorylation of the C-terminal domain of RNA polymerase II, as recently depicted. [13][14][15][16] Whereas metazoan CAK consists of a CDK7:Cyclin-H complex, activation of the budding yeast CDK1 (Cdc28) is mediated by the distantly related and monomeric CAK1 (hereafter scCAK1). [17][18][19] Besides phosphorylation, the CDK1:Cyclin-B kinase activity and substrate binding preferences are also regulated by various binding proteins.…”
Section: Introductionmentioning
confidence: 99%
“…CDK1 along with cyclin B plays a very important role in mitosis and meiosis at the transition of G2/M phase in the eukaryotic cell cycle (Liu et al, 2015; Petrone et al, 2016; Qiu et al, 2008). CDK7 associated with cyclin H comprises the CDK‐activating kinase (CAK), providing the T‐loop phosphorylation required for activation of CDKs 1,2, 4 and 6, which drive cell cycle progression (Peissert et al, 2020; Phinyo et al, 2014; Sava et al, 2020; Schachter & Fisher, 2013). Many studies have identified the role of CDK1 and CDK7 in cell cycle progression and transcription.…”
Section: Introductionmentioning
confidence: 99%